FPGA Implementation of an Inertia Emulation Control Strategy for a DC Microgrid - Samanta, Soumya; Datta, Subir; Roy, Binoy Krishna (IEEE transactions on energy conversion, 2024)
Inertia enhancement of a microgrid plays an important role in improving its stability. In this paper, an inertia emulation control technique is proposed for the inertia enhancement of a DC microgrid. The proposed control technique has three parts: (i) an inertia emulation control for the bidirectional DC-DC converter (ii) an inertia emulation control for the solar photovoltaic (PV) unit, and (iii) a coordinated inertia emulation for the inverter-connected AC load. The inertia emulation control for the PV and battery units, emulate inertia to maintain the DC link voltage profile along with improving the battery current profile and the coordinated inertia emulation for the inverter that regulates the AC voltage and frequency by emulating inertia characteristics with the help of the DC bus voltage profile. The proposed control technique is first simulated in Matlab/Simulink. Then it is converted to hardware descriptive language (HDL) and verified using an field programmable gate array (FPGA)-in-the-loop platform. Finally, it is implemented in a hardware experimental setup. It is observed that the proposed control technique is performing satisfactorily under source and load variations.